INFLUENCE OF INTERNAL AUDIT,GOOD CORPORATE GOVERNANCE, ANDCORPORATE SOCIAL RESPONSIBILITY ON THE FINANCIAL PERFORMANCE OF SHARIA BANKING IN INDONESIA FOR THE 2016-2020 PERIOD - Nuraini; Nur Melinda Lestari; Rahmat Dahlan; Ahmad Said Matondang; Eko Susanto (International Conference on Health Science, Green Economics, Educational Review and Technology, 2023)
This study aims to determine the effect of Internal Audit, Good Corporate Governance as measured by the Board og Commissioners, Board of Directors, and Sharia Supervisory Board and Corporate Social Responsibility on Financial Performance as measured by Return on Asset (ROA) of Islamic Banking listed in Indonesia for the 2016-2020 period. This research is included in the type of causality quantitative research. The data used is secondary data in the form of financial reports published by Islamic banking companies in Indonesia for the period 2016-2020. The population used is islamic banking companies in Indonesia as many as 14 Islamic banks, then with sampling techniques using purposive sampling method so as to get a selecteed sample of 10 Islamic banks. The dara analysis method used is panel data multiple linear regression. The results showed that the independent variables of Internal Audit, Board of Commissioners, Board of Directors have a significant as measured by Return on Asset (ROA). While the independent variables of the Sharia Supervisory Board and Corporate Social Responsibility have a negative, and insignificant effect on financial performance as measured by Return on Asset (ROA). Simultaneously, the independent variables of Internal Audit, Board of Commissioners, Board of Directors, Sharia Supervisory Board, and Corporate Social Repsonsibility have a significant effect and are able to explain ROA by 62.66% and the rest is explained by other factors not examined in this thesis.